2018
DOI: 10.1051/sicotj/2018032
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of bone resection in total knee arthroplasty using CT assisted-3D printed patient specific cutting guides

Abstract: Introduction: We conducted this study to determine if the pre-surgical patient specific instrumented planning based on Computed Tomography (CT) scans can accurately predict each of the femoral and tibial resections performed through 3D printed cutting guides. The technique helps in optimization of component positioning determined by accurate bone resection and hence overall alignment thereby reducing errors.Methods: Prophecy evolution medial pivot patient specific instrumented knee replacement systems were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Surgeons performing total knee arthroplasty (TKA) and considering different alignment options and instrumentation are interested in the accuracy and time it takes to make the distal and posterior femoral bone resections that determine the setting of the femoral component [ 7 ]. Technology proponents argue that robotic, navigation, and patient-specific instrumentation more accurately hit the femoral target than manual instruments [ 12 , 14 , 22 , 28 ]. Whereas manual instrument proponents argue that technology lengthens the operation, adds expense, and induces stacked errors arising from transforming images into a 3D model, planning the resection planes, and registering instruments [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons performing total knee arthroplasty (TKA) and considering different alignment options and instrumentation are interested in the accuracy and time it takes to make the distal and posterior femoral bone resections that determine the setting of the femoral component [ 7 ]. Technology proponents argue that robotic, navigation, and patient-specific instrumentation more accurately hit the femoral target than manual instruments [ 12 , 14 , 22 , 28 ]. Whereas manual instrument proponents argue that technology lengthens the operation, adds expense, and induces stacked errors arising from transforming images into a 3D model, planning the resection planes, and registering instruments [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the commonly used techniques to improve surgical accuracy include computer navigation ( 11 , 12 ), patient-specific cutting guides ( 13 , 14 ), and robotics ( 15 , 16 ). However, previous studies on the cost-effectiveness of these techniques have shown that either technique will increase the cost of each case, which mainly comes from the purchase and maintenance of machinery and equipment, additional preoperative imaging examinations, and limited implant choice of some closed robotic platform.…”
Section: Introductionmentioning
confidence: 99%
“…Again all those studies used the global axis as the reference axis and none of these investigated a threshold value of correction. Computer assisted guidance for implant positioning has been presented as an advanced solution [41]; a recent meta-analysis displayed better short term functional outcomes when using imageless computer navigation [42][43][44], but without being necessarily correlated with an optimal global alignment. In addition, patient-specific instrumentation (PSI) has been presented to improve accuracy in TKA but there utility is still controversial [45].…”
Section: Discussionmentioning
confidence: 99%